Assessment of the knowledge, attitude and practice of self medication among second year undergraduate medical students in a tertiary care teaching hospital - Gupta, Seema; Khajuria, Kanika; Bhat, Nusrat K.; Khajuria, Vijay; Mehra, Akanksha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Inappropriate self-medication is a cause of concern as it can result in wasteful expenditure, prolonged suffering, drug dependence, resistance and increase in morbidity. Self medication assumes significance among medical students as they have knowledge about ailments and medicines. The aim of the study was to assess the knowledge, attitude and practice of self-medication among undergraduate medical students. Methods: The present study was conducted in December 2017 among second professional undergraduate medical students in the Department of Pharmacology and Therapeutics, GMC Jammu after obtaining approval from the Institutional Ethics Committee of GMC, Jammu. A total of 123 students who took self-medication during last six months were included and given a questionnaire that included open and close ended questions about self-medication. Data was analysed using Microsoft Excel and presented as number and percentages. Results: Total of 123 second professional undergraduate MBBS students were analysed. 72 (58.53%) were males and 51 (41.46%) were females. 96 (78%) students practised self-medication. Allopathic drugs were most commonly used for self medication (93.5%), followed by Ayurvedic drugs. Fever and headache were common ailments treated with self medication. Common class of drugs used for self medication were antipyretics (66.6%), antibiotics (42.2%). Adverse drug reactions were perceived as the most common disadvantage of self medication. Analysis of source of information revealed that old prescriptions (33%), internet (18%) were the main sources of information. Regarding prevention of self medication, many students perceived that enhancing awareness was the most effective solution (72.3%) followed by stoppage of supply of medicines without prescription(39.8%). Conclusions: Self medication is practised by a majority of students. As responsible self medication is now increasingly being considered as a component of self-care, there is need for review of educational programs especially teaching of rational and judicious use of medicines to the undergraduate medical students.